Oxidação úmida em condições supercríticas: tratamento de efluentes e produção de H2 a partir de efluentes industriais e urbanos - Pinto, Leandro Ferreira (2014)
This work reports, new experimental data production of H2 and reduction of TOC (total organic carbon) from the gasification of lactose (synthetic wastewater) and whey (actual effluent) in supercritical water with or without the presence of catalysts (NaOH, KOH and Na2CO3) or oxidizing (H2OH and t-BHP) in a continuous flow reactor, built in Inconel 625. For the synthetic effluent (lactose) Reactions were carried out in a temperature range of 550 °C-700 °C, pressure 225 bar, lactose concentrations in the range of 5 g.L-1 - 25 g.L-1, feed streams of 5 g.min-1 and 7 g.min-1 and reaction time of 30 minutes. The optimum condition for the production of H2 (700 °C and 0.5%) had a yield of ≈ 4.5 (mol H2/mol lactose) and TOC reduction of ≈ ? 95%. However, the worst condition (550 °C and 25 g.L-1) had incomes of ≈ 0.5 (mol H2/mol lactose) and TOC reduction of ≈ 50%. In this operating condition the use of these catalysts or oxidizing increased yields of ≈ 0.5 to ≈ 5.0 (mol H2/mol lactose) as well as the reduction of TOC increased to ≈ 97%. In general, increasing the temperature increased quantities of H2 and CO decrease the amount. That is, the H2/CO ratio increases with increasing temperature and decrease in lactose concentration. For reactions involving whey gasification showed higher molar fractions of the data obtained for the reactions with lactose formed gases. The gases produced are mostly H2 and CO2 and trace amounts of CO and CH4. However, the behavior of the production of these gases is consistent for both effluents (real or synthetic). The mass flow rate of the produced gas is 60-65% of the mass flow rate of entry of whey. The remainder consisting of coke formed in the reactor and the treated effluent. The efficiency of treatment of whey, for lowering total organic carbon (TOC) decreased from 5259 mg.L-1 to 421 mg.L-1, reaching 85% reduction. In addition to the gasification reactions of lactose and whey oxidation of leachate (leachate) were performed, aiming to soil degradation. The application of supercritical oxidation of leachate samples showed satisfactory efficacy in reducing the physical and chemical parameters of COD, TOC, turbidity, color and absorbance. The manipulation of the feed flow (6 g.min-1 and 12 g.min-1), temperature (550 °C, 600 °C, 650 °C and 700 °C) and pressure (150 bar and 225 bar) allowed the achievement of high levels of degradation of the effluent reaching values close to 100%. As expected, the levels of reduction of physical-chemical parameters were increasingly altered with increasing temperature. That is, the higher the temperature, the higher the level of degradation. Among the flows studied no significant performance improvements were observed, as the two flow rates showed similar results. Unlike the flow, the pressure difference in the results presented for the reduction of COD, with a difference of approximately 11% between one and another pressure. In addition to the degradation of the effluent, the formation of gases, mainly CO2 was observed. However, the amount of gas produced is negligible when compared to the production of gas formed in the gasification reactions of lactose/milk whey. In general, in supercritical water gasification dairy effluent and waste water (leachate) is an efficient alternative to energy production, for the production of gases, particularly H2 and for effluent treatment. Thus, the results obtained in this study add information of relevance and importance to deploying units wastewater treatment and hydrogen production from the use of gasification/oxidation in supercritical water. The application of this technology involves the solution of problems in energy and environmental scope. Energy in scope, this technology has a direct impact, producing energy from biomass. Environmental scope, technology is proposed for the efficient destruction of industrial waste and wastewater (leachate) that impact on the environmental and social cost of public health.